Innowacje na rynku krótkoterminowych papierów dłużnych w Polsce - Pauka, Marek (Innovations on the Commercial Paper Market in Poland, 2007)
The world commercial paper market is full of innovations. The paper presents chosen innovative and attractive ideas. They base on the derivatieves (indexed-linked, credit derivatives). The author is looking for the effective conditions to implement those structures in Poland
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 294-302